2007
DOI: 10.1002/anie.200603794
|View full text |Cite
|
Sign up to set email alerts
|

Alcohols as Electrophiles in CC Bond‐Forming Reactions: The Hydrogen Autotransfer Process

Abstract: The hydrogen autotransfer process involves an initial oxidative hydrogen elimination, followed by different types of reactions, and is completed with a reductive hydrogen addition to give the final product. The sequence allows the alkylation of different nucleophilic agents using environmentally benign alcohols as electrophiles, mild conditions, and soft bases, with water produced as the only waste material. Recent examples of modulating the organometallic catalyst have also lent themselves to expansion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
176
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 536 publications
(178 citation statements)
references
References 78 publications
1
176
0
1
Order By: Relevance
“…Also, the replacement of toxic alkylating agents by readily available alcohols makes this a greener route for amine synthesis. 5 The overall transformation is based on a process called "borrowing hydrogen" 6 or "hydrogen autotransfer" 7 The first use of homogeneous catalysts for the alkylation of amines with alcohols was described in 1981, and since then a 30 number of metal-containing catalysts, including complexes of ruthenium, rhodium and iridium, have been evaluated in this transformation. 4 Elegant results from the groups of Beller, 8 Williams, 9 Kempe, 10 Fujita, 11 Martín-Matute, 12 Crabtree 13 and Yus 14 have made the alkylation of amines with alcohols an 35 efficient method for the synthesis of a variety of amines.…”
mentioning
confidence: 99%
“…Also, the replacement of toxic alkylating agents by readily available alcohols makes this a greener route for amine synthesis. 5 The overall transformation is based on a process called "borrowing hydrogen" 6 or "hydrogen autotransfer" 7 The first use of homogeneous catalysts for the alkylation of amines with alcohols was described in 1981, and since then a 30 number of metal-containing catalysts, including complexes of ruthenium, rhodium and iridium, have been evaluated in this transformation. 4 Elegant results from the groups of Beller, 8 Williams, 9 Kempe, 10 Fujita, 11 Martín-Matute, 12 Crabtree 13 and Yus 14 have made the alkylation of amines with alcohols an 35 efficient method for the synthesis of a variety of amines.…”
mentioning
confidence: 99%
“…The in situ generated carbonyl groups are reactive towards nucleophiles such as amines and lead to the formation of iminium cationic species or imines, affording the expected N-alkylated amines after reduction, with water as sole side product. Although several examples adopting this strategy have been documented for the construction of N-alkylated amines, [1][2][3][4][5][6][7][8][9][10] and C-alkylated products arising from alcohols, [11][12][13][14] a one-step process for the simultaneous alkylation of both the N atom and the unactivated C(3) carbon of secondary amines is so far unknown and corresponds to a formal C À H activation for the later. Such modifications are of a great interest and would afford new routes to get access to functionalized amines of known biological interest [15] which usually require multistep syntheses.…”
mentioning
confidence: 99%
“…[10] Likewise, C À C bond formation reactions have also been investigated starting from carbonucleophiles or ylides with alcohols by a similar strategy. [11][12][13][14] This transformation involves the conversion of alcohols into aldehydes or ketones as transient intermediates via an oxidative hydrogen elimination. The in situ generated carbonyl groups are reactive towards nucleophiles such as amines and lead to the formation of iminium cationic species or imines, affording the expected N-alkylated amines after reduction, with water as sole side product.…”
mentioning
confidence: 99%
“…4 During the course of our ongoing studies on ruthenium catalysis, we recently found an unusual type of transfer hydrogenation between ketones (or secondary alcohols) and primary alcohols (or aldehydes) accompanied by carbon-carbon bond formation under a ruthenium-catalyzed redox shuttle. [5][6][7][8] Under these circumstances, herein we report a ruthenium-catalyzed transfer hydrogenation of alkynes to trans-alkenes by a trialkylamine (Scheme 1). 9 The results of several attempted transfer hydrogenation of diphenylacetylene (1a) under various conditions are listed in Table 1.…”
mentioning
confidence: 99%
“…10 From the activity of several ruthenium precursors examined, RuCl 2 (PPh 3 ) 3 is revealed to be the catalyst of choice and other catalyst precursors such as RuH2(PPh3)4, RuCl2 (=CHPh)(PCy3)2, RuCl3․nH2O/3PPh3 and Ru3(CO)12 resulted in either lower yield or lower selectivity of products (runs [6][7][8][9].…”
mentioning
confidence: 99%